Twin domain imaging in topological insulator Bi2Te3 and Bi2Se3 epitaxial thin films by scanning X‐ray nanobeam microscopy and electron backscatter diffraction. Issue 2 (17th February 2017) - Kriegner, Dominik; Harcuba, Petr; Veselý, Jozef; Lesnik, Andreas; Bauer, Guenther; Springholz, Gunther; Holý, Václav
Abstract : Imaging with surface‐ and bulk‐sensitive electron and X‐ray diffraction based microscopic techniques enabled identification of the twin domain distribution of Bi2 Te3 and Bi2 Se3 thin films. Correlations between the surface topography and crystal orientation are established. Abstract : The twin distribution in topological insulators Bi2 Te3 and Bi2 Se3 was imaged by electron backscatter diffraction (EBSD) and scanning X‐ray diffraction microscopy (SXRM). The crystal orientation at the surface, determined by EBSD, is correlated with the surface topography, which shows triangular pyramidal features with edges oriented in two different orientations rotated in the surface plane by 60°. The bulk crystal orientation is mapped out using SXRM by measuring the diffracted X‐ray intensity of an asymmetric Bragg peak using a nano‐focused X‐ray beam scanned over the sample. By comparing bulk‐ and surface‐sensitive measurements of the same area, buried twin domains not visible on the surface are identified. The lateral twin domain size is found to increase with the film thickness.